On the Problem of Automatic Transformation of the Sentence - Bratus, T.; Tyshchuk, J. (My University, 2020)
The paper deals with the peculiarities of inversion in the English language. Inversion is regarded as a form of linguistic transformation The paper suggests an algorithm of automatic transformation of the sentence by the case of the negative type of stylistic inversion.
Keywords: inversion; linguistic transformations; automatic transformation; grammatical inversion; stylistic inversion; sentence